The particularity of Commercial Sports Company at founding. - Guermat, Ahmed Elamine (Journal of Human Sciences, 2020)
Professional sport has become a profitable activity, under the influence of economic globalization. The amateur sports club has become a professional club. As part of what is called the commercial sports company. which affected some of the traditional concepts of the association, especially during the establishment phase. This is in particular due to the characteristics associated with the general organization of sports competition as well as the role of amateur clubs in this society. It is the elite which makes possible the creation of the commercial sports company by the amateur club. If the role is effective at the founding phase, the sports society will base its contributions on the foundations of the amateur club through the club’s name or slogan, as well as on the popular basis. All this in the light of the laws governing this matter, in particular the provisions of the Commercial Code, and Law No. 13-05 regulating and developing physical and sporting activities, and the Decree No. 15-73 regulating the provisions applicable to the club professional athlete.